Psoriatic arthritis: a review - Amherd-Hoekstra, Anne; Näher, Helmut; Lorenz, Hanns-Martin; Enk, Alexander (Journal der Deutschen Dermatologischen Gesellschaft, 2010)
Psoriatic arthritis (PsA) is an immunologically triggered, chronic inflammatory arthropathy, which can have a lasting influence on the quality of life of affected individuals. An early diagnosis is essential in order to institute adequate therapy. Both dermatologists and rheumatologists should be involved in the diagnosis and management of the disorder. Mild forms can be managed with NSAID and systemic corticosteroids. In acute forms with a confirmed diagnosis and oligo- to polyarticular involvement, disease-modifying therapy with DMARD (Disease-Modifying Antirheumatic Drugs) is indicated. New studies of PsA show that tumor necrosis factor (TNF) plays a central role in mediating inflammation. For this reason, TNF-α antagonists have become more and more important as a second-line therapy for PsA.
Gesehen am 22.11.2022